Thermal decomposition, kinetics and electrical measurements of Poly(3-Acetamidopropyl Methacrylate)/graphite composites - Biryan, Fatih; Demirelli, Kadir (Taylor & Francis Ltd, 2019)
3-Acetamidopropyl methacrylate [AAPMA] (monomer) were synthesized. The homopolymer of AAPMA was prepared by free radical polymerization method. Novel composites based on poly(3-acetamidopropyl methacrylate) [PAAPMA] containing graphite nanoparticles were prepared using ultrasonic bath. The decomposition behavior of PAAPMA before and after adding graphite to PAAPMA was thermally investigated through thermogravimetric analysis measurements (TGA). Flynn-Wall-Ozawa method for thermal decomposition kinetics of poly(AAPMA) was applied to thermogravimetry curves. The activation energies for the first stage of poly(AAPMA), poly(AAPMA)/1.5% by wt graphite and poly(AAPMA)/6.0% by wt graphite are found to be 115?kJ/mol, 76.7?kJ/mol and 58.7?kJ/mol for conversion of 0.40, respectively. The activation energies in the second step are found to be 116?kJ/mol and 57?kJ/mol at the different conversion of 0.75, respectively. The thermal degradation of both poly(AAPMA) and poly(AAPMA)/graphite 6.0% by wt showed that monomer produced by main chain breaking. And also, in case of composite with graphite 6.0% by wt of poly(AAPMA) was observed that the more amount of monomer revealed at lower temperatures during degradation of composite. H-1, C-13-NMR, FT-IR and GC-MS analyses results showed that as major component of products formed during degradation of the pure polymer (to 365??C) and poly(AAPMA)/graphite 6.0% by wt (to 265??C) was AAPMA (monomer). Electrically conductivity of graphite-based poly(AAPMA) composites were investigated. So, dc and ac electrical conductivity and dielectric properties, i.e., real and imaginary parts of the permittivity of pure polymer and polymer composites were revealed. The ac dielectric measurements of poly(AAPMA) were investigated at room temperature between 100Hz and 2kHz depending on the alternating current conductivities. The dipolar functional groups (C-O, C?=?O and N-C?=?O) of the AAPMA segment showed that possess significantly effect on the dielectric constant. Also, the activation energy profile of different poly(AAPMA)/graphite composites was revealed by measuring dc conductivity of individual composite material.
Keywords: Thermal decomposition; activation energy; electrical measurements; kinetics